KINERJA SMA NEGERI 1 KABUPATEN KARANGANYAR PROVINSI JAWA TENGAH - ., Hermansyah (JI@P, 2023)
An analysis of the performance of public organizations is important to find information as an evaluation activity in order to assess the success of the implementation of its duties and functions. SMA N 1 Karanganyar is one of the leading public high schools in Karanganyar Regency with an A (Excellent) accreditation. This study aims to examine how the performance of SMA Negeri 1 Karanganyar Regency, Central Java Province. The research used a qualitative case study type method. The primary and secondary data, collected through interviews and documentation, and refers to various written sources. This research use performance analysis theory for the public sector, with indicators of responsiveness, responsibility, accountability, productivity, and service quality. The results found that SMA N 1 Karanganyar met good indicators in terms of responsiveness, responsibility, accountability, and productivity. However, limitations were found in terms of responsiveness which could still be optimized, due to limited socialization of complaint management. In addition, in terms of service quality, it is necessary to pay attention to empathy because there is no open academic dialogue and public relations to collect input from the wider community. So, there is no better service agenda and priority based on user input and the general public. Keyword: responsiveness, responsibility, accountability, productivity, service quality, SMAN 1 Karanganyar